Comparisons of high-risk cervical HPV infections in Caribbean and US populations - Jackson Maria; Gollin Susanne M; Garwood David; Fletcher Horace; Eckstein Stacy; Edwards Robert P; Bunker Clareann H; Markovic Nina; Watt Angela; Ragin Camille C; Patrick Alan L; Smikle M; et al. (Infectious Agents and Cancer, 2009)
Abstract Background Disparities in cervical cancer incidence and mortality rates exist among women of African ancestry (African-American, African-Caribbean and African). Persistent cervical infection with Human papillomavirus (HPV) is associated with cervical dysplasia and if untreated, could potentially progress to invasive cervical cancer. Very few studies have been conducted to examine the true prevalence of HPV infection in this population. Comparisons of cervical HPV infection and the type-specific distribution of HPV were performed between cancer-free Caribbean and US women. Results The Caribbean population consisted of 212 women from Tobago and 99 women from Jamaica. The US population tested, consisted of 82 women from Pittsburgh. The majority of the US subjects was Caucasian, 74% (61/82) while 12% (10/82) and 13% (11/82) were African-American or other ethnic groups, respectively. The age-adjusted prevalence of any HPV infection among women from Tobago was 35%, while for Jamaica, it was 81% (p < 0.0001). The age-adjusted prevalence of HPV infection for Caribbean subjects was not statistically significantly different from the US (any HPV: 47% vs. 39%, p > 0.1; high-risk HPVs: 27% vs. 25%, p > 0.1); no difference was observed between US-Blacks and Jamaicans (any HPV: 92% vs. 81%, p > 0.1; high-risk HPV: 50% vs. 53%, p > 0.1). However, US-Whites had a lower age-adjusted prevalence of HPV infections compared to Jamaican subjects (any HPV: 29% vs. 81%, p < 0.0001; high-risk HPV: 20% vs. 53%, p < 0.001). Subjects from Jamaica, Tobago, and US-Blacks had a higher proportion of high-risk HPV infections (Tobago: 20%, Jamaica: 58%, US-Blacks: 40%) compared to US-Whites (15%). Similar observations were made for the presence of infections with multiple high-risk HPV types (Tobago: 12%, Jamaica: 43%, US-Blacks: 30%, US-Whites: 8%). Although we observed similar prevalence of HPV16 infections among Caribbean and US-White women, there was a distinct distribution of high-risk HPV types when comparisons were made between the ethnic groups. Conclusion The higher prevalence of cervical HPV infections and multiple high-risk infections in Caribbean and US-Black women may contribute to the high incidence and prevalence of cervical cancer in these populations. Evaluation of a larger sample size is currently ongoing to confirm the distinct distribution of HPV types between ethnic groups.